The nature of healing power in the Holy Qur`an - Shogar, Ibrahim (2019)
Background: the faith-based healthcare approaches are growing consistently with evidence-based biomedical research and practices. Religion and spirituality are increasing becoming important in medical enterprise, not only to patients, but also to medical doctors. Centres for the integration of health and spirituality, religious oriented clinics, and Shari`ah compliant hospitals are established to apply not only the compassionate approaches to healthcare practices but also to improve healthcare outcomes. The Islamic medical heritage has a considerable legacy to contribute on this topic. The holy Qur`an has addressed the issue of healing based on the term (Shifa` / شفاء) in six occasions. The holy Qur`an describes itself as cure in four cases. The term (Shifa`) was used by Qur`an in two cases for physical healing. Today there are various methods of practicing, all are claimed to be Qur’ānic. Thus, further investigation on this topic is necessary. Objective: this paper aims to explore nature of healing power in the holy Qur`an, based on views of early Muslim scholars. The religious oriented medical centres are becoming more attractive across the global community, therefore it is necessary to understand the Islamic perspective on this matter based original sources of Islam, i.e. Qur`an and Sunnah. Methodology: Although faith-based medical research can be empirical or theoretical, the method adopted in this paper is theoretical in nature. It analyzes the Qur’ānic terminology “healing” (Shifa`) based on various perspectives of early Muslim scholars, comparatively with modern approaches of spiritual healing. Results & Conclusions: findings of the paper should emphasize that nature of Qur’ānic healing is not only spiritual but also intellectual and physical. It also suggests that selection of medical students and practicing medical doctors should be based on their interest in and understanding the healing power of faith.